Kebahagiaan Perkawinan Ditinjau Dari Faktor Komunikasi Pada Pasangan Suami Istri - Sri Andjariah (LPPM Universitas Proklamasi 45, 2005)
Marriage happiness is contributed largely by couple's communication smoothness. The marriage happiness scale is demonstrated through 5 aspects i.e. passionate love, authority distribution, sexual activity, financial situation, relationship with spouse's family. The couple's communication scale is translated through 4 aspects i.e. discussion, dialog, body language, and sexual activity. The Pearson correlation between the couple's communication and the marriage happiness variables indicates that r = 0.547 with p = 0.004. The determinant coefficient which explains the contribution of independent variable seems low (29.9%). It is suggested that other variables should be included such as the length of marriage (couple's age), couple's work pattern, communication method, and type of household. It is strong recommended that husbands should also be the research subjects. The husband's perception of marriage happiness might be different with his wife's.